Plankton Diversity in Litopenaeus vannamei Cultured Ponds - Saraswathy, R.; Muralidhar, M.; Ravichandran, P.; Lalitha, N.; Sabapathy, V. Kanaga; Nagavel, A. (International Journal of Bio-resource and Stress Management, 2023)
The culture of animals in ponds is vital in the context of increasing demand for seafood and declining trend of marine production. Aquaculture makes significant contribution to export earnings and employment in India. The annual production of shrimps from aquaculture in India is approximately 0.126 million metric tons. The production of P. monodon was stagnant over the last few years due to WSSV disease outbreaks and drastic fall in export prices. The growth rate of P. monodon was only 44%, whereas L. vannamei registered a growth rate of 1067% globally during the past decade. Considering the disease outbreaks in P. monodon and success of L. vannamei in other countries, it has been introduced in India recently. There is a lot of variation in plankton species under different systems of shrimp culture. To understand the diversity of plankton and its variation due to seasonal changes, L.vannamei ponds were monitored monthly for the occurrence of phytoplankton, zooplankton and benthos. In addition to this, other physico-chemical parameters of water were analyzed. During summer, a total of 29 different species of phytoplankton belonging to six different classes were observed. There were 15 different species of zooplankton belonging to two different classes namely Rotifera and Copepoda. The major groups of macro-benthos comprising of gastropoda, foraminifera, polychaeta, bivalvia and insecta were recorded during culture. During winter crop, Cladocera group was observed in addition to the summer crop zooplankton diversity. In summer crop, phytoplankton, zooplankton and benthos densities varied from 225-337x104cells ml-1, 72-342 cells l-1 and 47-79 numbers m-2 respectively, whereas in winter crop, phytoplankton, zooplankton and benthos densities varied from 74-105x104 cells ml-1, 64-189 cells l-1 and 13-26 numbers m-2 respectively. It is concluded that there is a significant variation in plankton population due to seasonal changes. Plankton abundance is higher in summer crop whereas diversity is more in winter crop.